2004
DOI: 10.1257/0895330042632744
|View full text |Cite
|
Sign up to set email alerts
|

The Purchasing Power Parity Debate

Abstract: P urchasing power parity (PPP) is a disarmingly simple theory that holds that the nominal exchange rate between two currencies should be equal to the ratio of aggregate price levels between the two countries, so that a unit of currency of one country will have the same purchasing power in a foreign country. The PPP theory has a long history in economics, dating back several centuries, but the specific terminology of purchasing power parity was introduced in the years after World War I during the international … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
397
0
14

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 795 publications
(447 citation statements)
references
References 79 publications
5
397
0
14
Order By: Relevance
“…The AFX Index is prepared at Liverpool John Moores University. 9 Recent evidence on PPP is reviewed in Taylor and Taylor (2004). prices are sensitive to volatility. Managers are at risk if they are long (short) volatility when volatility declines (increases).…”
Section: Currency Returns Factors and Methodologymentioning
confidence: 99%
“…The AFX Index is prepared at Liverpool John Moores University. 9 Recent evidence on PPP is reviewed in Taylor and Taylor (2004). prices are sensitive to volatility. Managers are at risk if they are long (short) volatility when volatility declines (increases).…”
Section: Currency Returns Factors and Methodologymentioning
confidence: 99%
“…However, there is not much research on highfrequency financial series, such as the intraday Forex trading, since the plentiful trade records (tick by tick) are not uniformly distributed (Dacorogona et al, 2001, Tsai 2002. Classical linear models such as the Purchasing Power Parity model (BahmaniOskooee et al, 2006, Choong et al, 2003, Taylor and Taylor, 2004 fail to explain the temporal currency fluctuations. It is demonstrated that nonlinear forecasting methods, as the one we propose here, are often better than linear ones for predicting the Forex trading series (Kamruzzaman andSarker, 2004, Boero andMarrocu, 2002).…”
Section: Predicting the Forex Intra-day Trading Seriesmentioning
confidence: 99%
“…These papers are among many which have found that the data on real exchange rates can 1 For recent surveys on the literature which highlight the dynamics of real exchange rates characterized as a nonlinear process, see Ahmad and Glosser (2011), Taylor (2006), and Taylor and Taylor (2004). Engel, Mark and West (2007) provide a thorough overview of the developments in both theoretical and empirical literature.…”
Section: Introductionmentioning
confidence: 99%